Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(97.13+130.13\)
\(=13\left(97+130\right)\)
\(=13.227\)
\(=2951\)
b, \(86.153-530.8,6\)
\(=86.153-53.10.8,6\)
\(=86.153-53.86\)
\(=86\left(153-53\right)\)
\(=86.100\)
\(=8600\)
trả lời:
a) 97.13 + 130.13
= 13.( 97 + 130 )
= 13. 227
= 2951
b) 86.153 - 530.8,6
= 86.153 - 53.10.8,6
=86. 153 - 53.86
= 86. ( 153 - 53 )
= 86.100
= 8600
học tốt!
a) \(49-\left(3x-1\right)^2=0\)
\(\Leftrightarrow7^2-\left(3x-1\right)^2=0\)
\(\Leftrightarrow\left(7-3x+1\right)\left(7+3x-1\right)=0\)
\(\Leftrightarrow\left(8-3x\right)\left(6+3x\right)=0\)
\(\hept{\begin{cases}8-3x=0\\6+3x=0\end{cases}}\Rightarrow\hept{\begin{cases}x=\frac{8}{3}\\x=-2\end{cases}}\)
Vậy \(x=\frac{8}{3};x=-2\)
b) \(\left(x-1\right)^3-\left(x+2\right)\left(x^2-2x+4\right)=3\left(1-x^2\right)\)
\(\Leftrightarrow\left(x-1\right)^3-\left(x^3+2^3\right)-3\left(1-x^2\right)=0\)
\(\Leftrightarrow x^3-3x^2+3x-1-x^3-8-3+3x^2=0\)
\(\Leftrightarrow3x-12=0\)
\(\Rightarrow x=4\)
Vậy \(x=4\)
\(\dfrac{-5x+7-2x+3-3x+4}{2-x}=\dfrac{-10x+14}{2-x}=\dfrac{-2\left(5x-7\right)}{2-x}=\dfrac{2\left(5x-7\right)}{x-2}.\)
B
vì sao bn nhỉ ?